Service Quality of the Gauteng Hotel Industry Supply Chain. - Mr L.E.M. Mosana; Dr A.E. Nesamvuni; Dr J.R. Roberson (African Journal of Hospitality, Tourism and Leisure, 2019)
The success of a hotel’s food operation unit depends on customer satisfaction and repeat patronage. There is a high probability that customers will be satisfied with their dining experience if the service and product quality provided by an hotel food operation unit are of an exceptional quality. The provision of high-quality products and service is only possible if the inputs from suppliers the food operation unit relies on, are also of the highest possible quality. Research-based articles on the quality of service by suppliers of hotel food operation units in Gauteng province, South Africa, could not be sourced. The researcher was therefore of the opinion that it is important to fill this gap in the existing body of knowledge by conducting a study on the perceived service quality provided by suppliers as experienced by hotel food operation unit managers. The study followed a quantitative approach and non-probability sampling was applied to selected participants from the population of 1 428 hotel food operation unit managers. Apilot study was completed, after which 178 SERVPERF questionnaires were analysed for the study. The findings of the research indicate that the hotel food operation unit managers’ perceived suppliers’ service positively in all five SERVPERF service quality dimensions.